High‐Pressure Characterization of the Cage‐Structured Explosive TEX by Dispersion‐Corrected DFT Calculations. Issue 2 (20th September 2020) - Wang, Wenpeng; Li, Hanwei; Liu, Qijun; Liu, Fusheng; Liu, Zhengtang
Abstract : 4, 10‐Dinitro‐2, 6, 8, 12‐tetraoxa‐4, 10‐diazaisowurtzitane (TEX) is one of the densest N ‐nitramine explosives. This work reports the structure, molecular interactions, equation of state, and electronic properties of TEX using dispersion‐corrected density functional theory (DFT‐D) calculations. The simulated lattice parameters and molecular interactions are in good agreement with the experimental data at ambient pressure. Furthermore, the high‐pressure characterization of TEX is studied as well. A good agreement of the simulated and experimental unit‐cell constants is obtained as a function of pressure up to 10 GPa, and a structural change is identified at around 1.5 GPa. The pressure dependence of the molecular geometries and interactions confirm this change and suggest that it involves a pressure‐induced distorted nitro functional group. Moreover, the equation of state of TEX in the range of 0–10 GPa is determined by fitting the pressure–volume ( P–V ) data to the Birch–Murnahan equation of state. From the first‐principles bandgap criterion, the impact sensitivity of TEX under high pressure is predicted. Abstract : The crystal and molecular structure, equations of state, and molecular interactions of the cage‐structured explosive TEX (i.e., 4, 10‐dinitro‐2, 6, 8, 12‐tetraoxa‐4, 10‐diazaisowurtzitane) are studied using dispersion‐corrected density functional theory calculations. A pressure‐induced conformation change is identified around 1.5 GPa. The intermolecular interactions and impact sensitivity of TEX are also discussed in this work.